Problems in adjunct cartography : a case study / Ng Pei Fang - Ng, Pei Fang (2012)
Beginning students of syntax may find that tree diagram drawing is a daunting task. Problems in tree diagram drawing are common when they are given exercises in cartography drawing; the three problems facing these students are: (1) unable to differentiate a complement from an adjunct and thus treat both as the same syntactic element; (2) not sensitive that for an ambiguous clause, there are two possible adjunction operations where an XP can be adjoined to a V′ and N′; thus they are unable to disambiguate an ambiguous clause by producing two cartographies with different internal structures; (3) not sensitive to the two possible adjunction operations when a head X is preceded and followed by an adjunct where either one can be adjoined first depending on the interpretations given to the clause. This research report attempts to explore if postgraduate students who have been exposed to the X-bar theory and practices in producing cartographies manage to overcome the problems (1), (2), (3) after they studied the syntax of English. An instrument which consists of phrases and clauses was designed and tested on the participants who studied TXGB 6303 Structure of English. The purpose of the study is to examine whether the participants have the three problems mentioned above. The results show that indeed the participants have the three problems. Examining the corpus of tree diagrams produced, it is found that the participants clearly do not have a strong understanding of the X-bar theory; they are unable to produce viable cartographies based on the three phrase structure rules which are the backbones of the theory.